The density trade-off does high rise construction contribute more than that of single dwellings to greenhouse gas emissions? - Beattie, C.; Newman, Peter (State of Australian Cities National Conference 2011, 2011)
Density increases are generally accepted as reducing the carbon involved in urban transport. This relationship has been shown consistently between cities (through the Global Cities database) and within cities like Sydney and Melbourne. However the density increases in buildings are more controversial with several studies suggesting that high rise buildings are much more greenhouse intensive due to their shared spaces such as lift lobbies and underground car parks and their extra embodied energy in the structure. There is thus confusion amongst policy makers who see a trade-off between increasing density for transport Greenhouse Gas emissions (GHGe) savings but reducing density for building GHGe. This confusion is further exacerbated by the lack of data supporting this viewpoint or indeed, any specific threshold beyond which an increase in density would mean an increase in GHGe. The resolution of this trade-off is examined by showing a) that the increase in GHGe associated with high rise living is not as significant as some of the recent Australian literature suggests; b) the transport gains in GHGe are far greater due to density than any losses in GHGe due to the high rise buildings; and c) when appropriate low carbon design is applied, the attributes of density and high rise significantly reduce greenhouse gas emissions compared with low density, detached dwelling, especially when the dramatic reductions due to co-generation are factored in.